The Role of Laboratory Simulation in The Development of Caring Behavior in Nursing Students: A Scoping Review: - Heman Pailak; Yakobus Siswadi (Faculty of Nursing, Universitas Pelita Harapan, 2025)
Caring behavior is a fundamental value in nursing practice and education. Simulation has emerged as an effective strategy to enhance not only clinical competence but also empathy, communication, and self-awareness in nursing students. This scoping review aims to explore the role of laboratory simulation in developing caring behaviors among nursing students and to identify the types of simulation used and related outcomes. Following the Joanna Briggs Institute (JBI) methodology, literature was searched in four databases (PubMed, EBSCO, ScienceDirect, and ProQuest) for studies published between 2015 and 2025. Inclusion criteria focused on nursing students, simulation-based learning, and caring or empathy outcomes. Twelve studies were included, predominantly quantitative in design (n = 10), along with one qualitative and one mixed-method study. Sample sizes ranged from 26 to 248 participants. Simulations used included high-fidelity (n = 4), virtual reality (n = 3), standardized patients (n = 3), and low-fidelity or role-play (n = 2). Most studies showed positive effects on empathy, communication skills, and caring behavior, especially with immersive or high-fidelity simulations. Overall, simulation-based learning, particularly high-fidelity and immersive methods, supports the development of caring behavior in nursing students. Its integration into nursing curricula is essential to prepare nurses for patient-centered, empathetic care.